UJI AKTIVITAS EKSTRAK DAN FRAKSINASI DAUN BRUCEA JAVANICA (Merril) SECARA INVITRO - Megawati Megawati; M Angelina (Jurnal Kimia Terapan Indonesia, 2010)
Brucea javanica (Merril) is a tropical plant widely grown in Indonesia, Brucea javanica has a bitter taste efficacious to reduce the heat and remove toxins, lethal parasites, anti-anti-dysentery and malaria. Chemical compounds contained in many of which have bioactivity. Antidiabetic test has been performed with a-glucosidase method, anti-oxidant test method "DPPH free radical scavenger" and BSLT toxicity test method (Brine Shrimp Lethality Test) of ethanol extractB.javanica. In the ethanol extract of leaves of the partition B.javanica performed using hexane, ethyl acetate and butanol. Then test each fraction in vitro activity. Test results showed that activity of ethylacetate is active as an anti-oxidant with IC50 value of 89,75 ppm and 7,52 ppm LC50 toxic values while antidiabetic did not have activites.Keyword : Antidiabetic, anti-oxidant, toxicity, a-glukosidase, DPPH, Brine Shrimp Lethality Test, Brucea Javanica(Merril).